2005
DOI: 10.1093/toxsci/kfi226
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Hyperoxic Lung Injury by the CYP1A Inducer β–Naphthoflavone

Abstract: Supplemental oxygen, frequently used in premature infants, has been implicated in the development of bronchopulmonary dysplasia (BPD). While the mechanisms of oxygen-induced lung injury are not known, reactive oxygen species (ROS) are most likely involved in the process. Here, we tested the hypothesis that upregulation of cytochrome P450 (CYP) 1A isoforms in lung and liver may lead to protection against hyperoxic lung injury. Adult male Sprague-Dawley rats were pretreated with the CYP1A inducer beta-naphthofla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 31 publications
3
46
0
Order By: Relevance
“…Lung microsomes were prepared by differential centrifugation, as reported previously (17), from individual animals. Protein concentrations and EROD (CYP1A1) activities in lung were assayed as we have described previously (17,19,20).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Lung microsomes were prepared by differential centrifugation, as reported previously (17), from individual animals. Protein concentrations and EROD (CYP1A1) activities in lung were assayed as we have described previously (17,19,20).…”
Section: Methodsmentioning
confidence: 99%
“…Lung microsomes (20 g of protein) prepared from individual animals were subjected to Western blotting, as described previously (17,19,20). The proteins bands on the blots were detected by chemiluminescence after exposure to x-ray films (ECL plus detection, Amersham Pharmacia Biotech, Inc., Piscataway, NJ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have indicated that α-Napthoflavone inhibits OS and serves potential roles is estrogen-induced breast carcinogenesis and ultraviolet-led human skin aging (27,28). β-Naphthoflavone has been demonstrated to protect mice against aristolochic acid-I-induced acute kidney injury, and to attenuate hyperoxic lung injury in premature infants primarily via mitigating OS (29,30). In the present study, α-and β-Naphthoflavone were identified to effectively antagonize the apoptosis-promoting effect of H 2 O 2 on neuronal SH-SY5Y cells.…”
Section: Discussionmentioning
confidence: 99%